The Effects of Using Quizlet on Vocabulary Knowledge Performance of College EFL Learners in Shandong Province, China - HUANTING, PAN (Universiti Malaysia Sarawak, 2024)
This study investigates the effect of Quizlet on the receptive and productive vocabulary knowledge of college EFL learners at a higher learning institution in Shandong Province, China, guided by Nation’s vocabulary knowledge framework. It also examines learners’ perceptions of Quizlet through an adapted Technology Acceptance Model (TAM). The research addresses four key questions: (1) the difference in receptive vocabulary performance between learners using Quizlet and traditional methods, (2) the difference in productive vocabulary performance between these groups, (3) learners’ perceptions of Quizlet, including perceived ease of use, usefulness, attitudes, behavioral intention, and actual usage, and (4) differences in these perceptions between high- and low-proficiency learners. A quasi-experimental design was employed with 191 participants from four classes, divided into an experimental group using Quizlet and a control group using paper-based word lists over eight weeks. Vocabulary performance was assessed through receptive and productive recall tests, while perceptions were gathered via questionnaires and semi-structured interviews. Results indicated that Quizlet significantly enhanced vocabulary knowledge, with the experimental group outperforming the control group in both receptive and productive tests. Additionally, learners expressed positive attitudes towards Quizlet, particularly regarding ease of use, usefulness in vocabulary learning, and a strong intention to continue using it. High-proficiency learners, in particular, showed a greater inclination to continue using Quizlet compared to their low-proficiency peers. These findings suggest that integrating Quizlet into college English courses not only enhances vocabulary acquisition but is also well-received by students, highlighting its potential as a valuable educational tool.